Review of the status of neoadjuvant therapy in HER2-positive breast cancer - Dowling, Gavin P.; Keelan, Stephen; Toomey, Sinead; Daly, Gordon R.; Hennessy, Bryan T.; Hill, Arnold D. K. (Frontiers in Oncology, 2023)
Purpose The development of human epidermal growth factor receptor 2 (HER2)-directed therapies has revolutionised the treatment of HER2-positive breast cancer. The aim of this article is to review the continually evolving treatment strategies in the neoadjuvant setting of HER2-positive breast cancer, as well as the current challenges and future perspectives. Methods Searches were undertaken on PubMed and Clinicaltrials.gov for relevant publications and trials. Findings The current standard of care in high-risk HER2-positive breast cancer is to combine chemotherapy with dual anti-HER2 therapy, for a synergistic anti-tumour effect. We discuss the pivotal trials which led to the adoption of this approach, as well as the benefit of these neoadjuvant strategies for guiding appropriate adjuvant therapy. De-escalation strategies are currently being investigated to avoid over treatment, and aim to safely reduce chemotherapy, while optimising HER2-targeted therapies. The development and validation of a reliable biomarker is essential to enable these de-escalation strategies and personalisation of treatment. In addition, promising novel therapies are currently being explored to further improve outcomes in HER2-positive breast cancer.